2001
DOI: 10.1007/s002800000262
|View full text |Cite
|
Sign up to set email alerts
|

Fendiline, an anti-anginal drug, increases intracellular Ca 2+ in PC3 human prostate cancer cells

Abstract: The anti-anginal drug fendiline induced internal Ca2+ release and external Ca2+ entry. Because prolonged increases in [Ca2+]i may lead to cell injury and death, the long-term effect of fendiline on the function of prostate cancer cells should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies on the association between antihypertensive drug usage and prostate cancer risk remain controversial. In vitro studies, CCB enhanced apoptosis of prostate cancer cells and might have a protective effect on prostate cancer [ 13 ]. Debes et al found that CCB significantly decreased the risk of prostate cancer, and their results varied by family history of prostate cancer [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the association between antihypertensive drug usage and prostate cancer risk remain controversial. In vitro studies, CCB enhanced apoptosis of prostate cancer cells and might have a protective effect on prostate cancer [ 13 ]. Debes et al found that CCB significantly decreased the risk of prostate cancer, and their results varied by family history of prostate cancer [ 14 ].…”
Section: Introductionmentioning
confidence: 99%